Core stability training on lower limb balance strength. Issue 7 (2nd April 2016) - Dello Iacono, Antonio; Padulo, Johnny; Ayalon, Moshe
Abstract: This study aimed to assess the effects of core stability training on lower limbs' muscular asymmetries and imbalances in team sport. Twenty footballers were divided into two groups, either core stability or control group. Before each daily practice, core stability group ( n  = 10) performed a core stability training programme, while control group ( n  = 10) did a standard warm-up. The effects of the core stability training programme were assessed by performing isokinetic tests and single-leg countermovement jumps. Significant improvement was found for knee extensors peak torque at 3.14 rad · s −1 (14%; P  < 0.05), knee flexors peak torque at 1.05 and 3.14 rad · s −1 (19% and 22% with P  < 0.01 and P  < 0.01, respectively) and peak torque flexors/extensors ratios at 1.05 and 3.14 rad · s −1 (7.7% and 8.5% with P  < 0.05 and P  < 0.05, respectively) only in the core stability group. The jump tests showed a significant reduction in the strength asymmetries in core stability group (−71.4%; P  = 0.02) while a concurrent increase was seen in the control group (33.3%; P  < 0.05). This study provides practical evidence in combining core exercises for optimal lower limbs strength balance development in young soccer players.